Optimization of exposure techniques for lumbosacral spine radiographic examination: a phantom study - Luechabhun, Chawee; Prasertdumrongchai, Supaksorn; Pukleeb, Bussarin; Suwanpradit, Petcharleeya; Apipunyasopon, Lukkana (The Thai Journal of Radiological Technology, 2024)
Background: X-ray imaging of the Lumbosacral spine (LS-spine) is a routine procedure in patients. The patient dose received from this examination is higher than that of X-rays taken in other areas. Therefore, it is essential to determine the appropriate exposure technique by considering both the radiation dose received and the image quality. Objective: The aim of this study was to identify the optimal parameters for LS-spine X-ray imaging, the radiation dose and image quality should be evaluated based on routine and modified protocols at King Chulalongkorn Memorial Hospital. Methods: A digital X-ray system (Digital Diagnost, Philips) with an image receptor and the human-like phantom (PBU-60, Kyoto Kagaku) were used. Both LS-spine anteroposterior (AP) and lateral projections were performed using both routine and modified protocols. The kerma area product (KAP), exposure index (EI), and deviation index (DI) were recorded simultaneously. The qualitative image quality was scored by three experienced radiographers. Results: LS-spine X-ray imaging in the AP projection with an applied voltage of 66 kVp and an increased filter thickness of 0.2 mmCu +1 mmAl, along with the use of the AEC system, provides appropriate DI and KAP values and yields the highest quality assessment scores. In the lateral projection, using 66 kVp and a filter thickness of 0.2 mmCu +1 mmAl along with the AEC system, yields appropriate DI and KAP values and results in satisfactory image quality. Conclusion: Using the AEC system combined with increased filter thickness for LS-spine X-ray imaging in both AP and lateral projections helps to reduce the radiation dose while providing images of appropriate quality.